Pemberdayaan Kelompok Tani Hutan Melalui Peningkatan Kapasitas Ketrampilan pada Penyeduhan Kopi Robusta - Maksum, Ali; Purbowati, Ike Sitoresmi Mulyo; Jaya, Gigieh Henggar; Novitasari, Dian (LPPM Universitas Trunojoyo Madura, 2025)
The growth of coffee consumption in Indonesia in 2025 is projected to reach an average of 7% per year with total coffee consumption reaching 450,000 tons/year. The shift in coffee consumption patterns of generation Z from tubruk coffee to various coffee brewing variants such as cold brew, filter coffee, and iced coffee is an obstacle for KTH Tani Jaya in marketing coffee products at the Kepuh Tourism Location. Based on direct observations in the field, there are problems, namely: The Forest Farmers Group